2013
DOI: 10.1038/bjc.2013.569
|View full text |Cite
|
Sign up to set email alerts
|

Emergency presentation of cancer and short-term mortality

Abstract: Background:The short-term survival following a cancer diagnosis in England is lower than that in comparable countries, with the difference in excess mortality primarily occurring in the months immediately after diagnosis. We assess the impact of emergency presentation (EP) on the excess mortality in England over the course of the year following diagnosis.Methods:All colorectal and cervical cancers presenting in England and all breast, lung, and prostate cancers in the East of England in 2006–2008 are included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
177
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(203 citation statements)
references
References 31 publications
19
177
1
6
Order By: Relevance
“…However, due to the low coverage, low dependence, high specificity subjective judgment and the discomfort of the patients, the method is not widely used in the clinic (4)(5)(6)(7). The Thinprep liquid-based cytological test (TCT) provides the screening efficiency of cervical cytology with a better medium for cervical cells and avoidance of the disadvantages of the Pap smear test.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the low coverage, low dependence, high specificity subjective judgment and the discomfort of the patients, the method is not widely used in the clinic (4)(5)(6)(7). The Thinprep liquid-based cytological test (TCT) provides the screening efficiency of cervical cytology with a better medium for cervical cells and avoidance of the disadvantages of the Pap smear test.…”
Section: Introductionmentioning
confidence: 99%
“…The survival of lung cancer patients presenting through an emergency route was examined separately for all non-resected lung cancer patients. Moreover, since previous studies have shown the largest differences in survival between groups of lung cancer patients in the first months after diagnosis [3,9], the association between emergency presentation and survival was investigated overall and for three time periods of follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency CRC surgery is a clinical challenges (18,19) that associated with advanced stage and high morbidity and mortality (20,21,22) and a high postoperative complications rate (10,23). Our study revealed that emergency CRC surgery is more worse outcomes than elective CRC surgery group in all stages.…”
Section: Discussionmentioning
confidence: 63%